2013
DOI: 10.1186/1471-2229-13-224
|View full text |Cite
|
Sign up to set email alerts
|

Automated analysis of calcium spiking profiles with CaSA software: two case studies from root-microbe symbioses

Abstract: BackgroundRepeated oscillations in intracellular calcium (Ca2+) concentration, known as Ca2+ spiking signals, have been described in plants for a limited number of cellular responses to biotic or abiotic stimuli and most notably the common symbiotic signaling pathway (CSSP) which mediates the recognition by their plant hosts of two endosymbiotic microbes, arbuscular mycorrhizal (AM) fungi and nitrogen fixing rhizobia. The detailed analysis of the complexity and variability of the Ca2+ spiking patterns which ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…S5 illustrates the distribution of waiting time autocorrelation values in our populations of spiking profiles. A high number of cells in all treatments demonstrated negative autocorrelation values, indicating that spiking responses to all fungal exudates are in most cases irregular, in analogy to what was described for AM fungal‐induced spiking profiles, and in contrast with the mostly regular rhizobium‐induced calcium spiking signals in the same experimental system (Russo et al , ). Statistical analysis showed no dependency between the distribution of waiting time autocorrelation values and the fungal exudate tested.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…S5 illustrates the distribution of waiting time autocorrelation values in our populations of spiking profiles. A high number of cells in all treatments demonstrated negative autocorrelation values, indicating that spiking responses to all fungal exudates are in most cases irregular, in analogy to what was described for AM fungal‐induced spiking profiles, and in contrast with the mostly regular rhizobium‐induced calcium spiking signals in the same experimental system (Russo et al , ). Statistical analysis showed no dependency between the distribution of waiting time autocorrelation values and the fungal exudate tested.…”
Section: Resultssupporting
confidence: 57%
“…Calcium spiking measurements were analyzed further using CaSA software (Russo et al , ). The generation of at least three peaks was the threshold for discrimination between responding and nonresponding cells.…”
Section: Methodsmentioning
confidence: 99%
“…However, high levels of Pi do not affect root calcium-spiking responses to AM fungi, indicating that Pi might not affect presymbiotic signaling through the common signaling pathway, which is required for AM fungi infection. Recently, a significant inhibition of presymbiotic signaling, such as the percentage of the calcium-spiking cells and average number of peaks in response to high Pi level, was also reported (Balzergue et al, 2013;Russo et al, 2013). Interestingly, it was reported that Pi inhibition of the arbuscular specific phosphate transporter gene PhPT5 may underlie reduced arbuscule colonization in Petunia hybrida, because the repression of PhPT5 precedes the reduction of AM colonization (Breuillin et al, 2010).…”
Section: Regulation Of Nutrient Exchange By Pi and N In Am Symbiosismentioning
confidence: 99%
“…Available tools for such an automatic analysis of spiking data are typically tailored towards spiking dynamics of neuronal membrane potentials ( Cajigas et al , 2012 ) but do not reflect the specific needs for Ca 2+ signals that often exhibit more noise and slow underlying trends. A recent approach addresses Ca 2+ spike recognition by Matlab scripts ( Russo et al , 2013 ), but without an interactive graphical user-interface (GUI), limiting the application to computational scientists. In particular, these approaches do not allow for an intuitive optimization of signal analysis nor a systematic analysis of the σ- T av relation.…”
Section: Introductionmentioning
confidence: 99%